Real Impact of Novel Immunotherapy Drugs in Cancer. The Experience of 10 Last Years - Andreas Koulouris; Christos Tsagkaris; Michail Nikolaou (Toxins, 2021)
Intense research on immunotherapy has been conducted during recent years. As advances in the field have started changing the landscape of cancer therapy, it is necessary to assess the impact of immunotherapeutic modalities in the treatment of various cancers. Ten years ago, in 2011, ipilimumab was the first of the newest immunotherapeutic drugs against cancer to be approved by the FDA. Then several drugs followed and formed a therapeutic arsenal to fight cancer. Initial studies were performed on metastatic patients, but there are currently several studies in patients with potentially curable cancers. All these developments have created a new environment for oncology which we will present in this article. This review examines the current evidence related to the impact of immunotherapy on various cancers and discusses its potential clinical and research implications, including its effectiveness in comparison to other treatment modalities (chemotherapy, radiotherapy), its toxicity and prospective research opportunities. While constant updates and further research is critical to understand the impact of immunotherapy in cancer therapy, not only does it seem to be important to assess the current state of knowledge highlighting the success but also to determine the challenging aspects of cancer immunotherapy.